ChemInform Abstract: Hydrotrifluoromethylthiolation of α‐Diazo Esters — Synthesis of α‐SCF3 Substituted Esters. Issue 47 (6th November 2014) - Lefebvre, Quentin; Fava, Eleonora; Nikolaienko, Pavlo; Rueping, Magnus
Abstract The reaction of aryldiazoacetates (I) with copper trifluoromethylthiolate (II) affords desired α‐(trifluoromethylthio)esters (III).